The effectiveness of pedicle screw immersion in vancomycin and ceftriaxone solution for the prevention of postoperative spinal infection: A prospective comparative study - Burak Eren; Feyza Karagöz Güzey; Serkan Kitiş; Nezih Özkan; Cafer Korkut (Acta Orthopaedica et Traumatologica Turcica, 2018)
Objective: The aim of this study was to evaluate the efficacy of the local application of vancomycin hydrochloride (HCl)–ceftriaxone disodium hemiheptahydrate onto implants before using them to prevent postoperative infection. Methods: The study included 239 patients (153 women and 86 men; mean age: 48.23 ± 16.77 years) who had thoracolumbar stabilization with transpedicular screws. All surgeries were performed by the same surgeon. Patients were divided into two groups. In the group 1 (n = 104), implants were bathed in a solution of local prophylactic antibiotics for 5 seconds just before implantation. In the group 2 (n = 135), implants were not bathed before implantation. Local antibiotics used in the study was effective against gram positive bacteria (including methicillin resistant Staphylococcus aureus) and gram negative bacteria. The rate of surgical site infection and wound healing time were compared between the groups. Results: A total of 10 patients (4.1%) had deep wound infection and 20 (8.4%) had superficial infection. The most common bacteria was Staphylococcus aureus. One patient died 21 days after the surgery because of sepsis. The wound healed in a mean of 9.66 ± 2.04 days in patients who had no infection and in 32.33 ± 19.64 days in patients with infection (p < 0.001). The patients in group 1 had significantly less deep infection than the patients in group 2 (p < 0.05). However, there was no statistically significant difference between the groups for superficial infection. Patients with vertebral fracture had significantly lower deep infection rate in group 1. The deep infection rate of group 1 patients with diabetes, with bleeding of more than 2000 mL, transfused with blood transfusions above 3 units and with dural injury was significantly lower than those in the group 2. None of the patients had allergic reactions to the drugs used for local prophylaxis. Conclusions: This study shown that bathing implants in antibiotics solution was an effective local prophylactic method to prevent deep infections in spinal surgeries with instrumentation. Level of Evidence: Level III, Therapeutic study. Keywords: Spinal infection, Implant associated infections, Surgical site infection, Prevent infection, Local antibiotic, Prophylactic antibiotic